Perbandingan Part Method dan Whole Method Untuk Meningkatkan Keterampilan Seni Nomor Tunggal Pada Cabang Olahraga Pencak Silat - Annisa Nur Halimah; Ira Purnamasari; Muhammad Tafaqur (Jurnal Kepelatihan Olahraga, 2022)
The purpose of this study was to determine “Comparison of Part Methodand Whole Method to Improve Single Number Art Skills in Pencak SilatSports”. The research method used is an experimental research method.The population in this study were Pencak Silat athletes in Cimahi city asmany as 10 people. The sample that the researcher uses is 8 people usinga purposive sampling approach with the criteria determined in this sampling technique. The sample is a Pencak Silat Athlete in Cimahi City in the single art category. The instrument used in this research is a single category Pencak Silat Scoring Sheet. The data analysis test used the paired sample t test and to find the difference in the average used the independent sample t test. It can be concluded that there is an effect of the  Part Method on increasing single number art skills in the sport of pencak silat, then there is no effect of the whole training method (Whole Method) on increasing single number art skills in the sport of pencak silat, and the final result there is a difference in the effect of the Part Method and the Whole Method on the improvement of single number art skills in the sport of pencak silat.